Utilization of agricultural lignocellulosic wastes for biofuels and green diesel production - Pocha C.K.R.; Chia S.R.; Chia W.Y.; Koyande A.K.; Nomanbhay S.; Chew K.W. (Elsevier Ltd, 2023)
Agricultural wastes; Biodiesel; Bioethanol; Crops; Deforestation; Diesel engines; Vegetables; Agricultural activities; Biological conversion; Diesel production; Fruit waste; Fuel properties; Green diesels; Human population; Lignocellulosic wastes; Thermochemical Conversion; Vegetable wastes; Fruits; biodiesel; bioethanol; biofuel; biogas; lignocellulose; lignin; biofuel; cellulose; deforestation; innovation; landfill; vegetable; Article; crop; fruit waste; vegetable waste; agriculture; human; prospective study; Agriculture; Biofuels; Humans; Lignin; Prospective Studies